New international business english: Teacher's guide video - Jones, Leo (New York: Cambridge University Press, 2000)
Este texto contiene los siguientes temas: Face to face, letters, faxes and memos,on the phone,summaries,notes,reports,working together,international trade,money matters,dealing with problems,visits and travel,marketing,meeting
Keywords: Inglés - Lenguaje